2023
DOI: 10.55908/sdgs.v11i3.733
|View full text |Cite
|
Sign up to set email alerts
|

Employees Performance as Affected by Monetary and Psychological Incentives (the Field of Study the Commercial Banks in UAE) a Comprehensive Review Study

Abstract: Purpose: The study investigated the Impact of Monetary and Psychological Incentives on Employees’ performance.  The problem of the study that is there is any statistically significant impact of the monetary incentives on employees' performance. Is there any statistically significant impact of the psychological incentives on employees' performance?  The study aimed to examine the impact of monetary incentives on employees' performance. To determine the impact of psychological incentives on employees' performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…This concept links activities and goals through the tasks of employees within the organization. In other words, these are the responsibilities, activities, and tasks of individuals that comprise their jobs, which must be done correctly taking into account the capabilities of employees who are qualified to do so [20]. The emergence of conflict or problems in the family is a common thing.…”
Section: Theoritical Frameworkmentioning
confidence: 99%
“…This concept links activities and goals through the tasks of employees within the organization. In other words, these are the responsibilities, activities, and tasks of individuals that comprise their jobs, which must be done correctly taking into account the capabilities of employees who are qualified to do so [20]. The emergence of conflict or problems in the family is a common thing.…”
Section: Theoritical Frameworkmentioning
confidence: 99%
“…James et al, (2012) performance leads to success in carrying out tasks and achieving planned goals. Thus in general it can be interpreted, that the performance of employee responsibilities which is the end result of work productivity both in quality and quantity, (Abdelhay et al, 2023;Popov, 2023;Tahir et al, 2023). Employee performance is feedback and is an important factor for the sustainability and development of the organization in the future.…”
Section: Employee Performancementioning
confidence: 99%
“…Resources Divisions are now focusing to recognize and improve this complete journey experience to have greater Employee Performance (Harlianto & Rudi, 2023). Other studies have focused on incentives and concluded that the absence of suitable incentives may negatively affect the hardworking employee's performance (Abdelhay, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%